Outcome of implants placed to retain craniofacial prostheses – A retrospective cohort study with a follow‐up of up to 30 years. (14th June 2022) - Alberga, Jamie; Eggels, Iris; Visser, Anita; van Minnen, Baucke; Korfage, Anke; Vissink, Arjan; Raghoebar, Gerry
Abstract: Objectives: To retrospectively assess the treatment outcomes of endosseous implants placed to retain craniofacial prostheses. Material and Methods: Patients with craniofacial defects resulting from congenital disease, trauma, or oncologic treatment had implant retained prostheses placed in the mastoid, orbital, or nasal region and then assessed over a period of up to 30 years. Implant survival rates were calculated with the Kaplan–Meier method. Clinical assessments consisted of scoring skin reactions under the prosthesis and the peri‐implant skin reactions. Possible risk factors for implant loss were identified. Patient satisfaction was evaluated using a 10‐point VAS‐scale. Results: A total of 525 implants placed in 201 patients were included. The median follow up was 71 months (IQR 28–174 months). Implants placed in the mastoid and nasal region showed the highest overall implant survival rates (10‐year implant survival rates of 93.7% and 92.5%, respectively), while the orbital implants had the lowest overall survival rate (84.2%). Radiotherapy was a significant risk factor for implant loss (HR 3.14, p < 0.001). No differences in implant loss were found between pre‐ and post‐operative radiotherapy ( p = 0.89). Soft tissue problems were not frequently encountered, and the patients were highly satisfied with their implant‐retained prosthesis. Conclusion: Implants used to retain craniofacial prostheses have high survival and patient satisfaction rates and can thus be considered as a predictable treatment option. Radiation is the most important risk factor for implant loss.